AN INVESTIGATION INTO THE IMPACT OF COGNITIVE STRATEGIES ON IRANIAN FEMALE HIGH SCHOOL STUDENTS’ READING COMPREHENSION - Sharifi, Asma (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2025)
This study explored the impact of cognitive strategies on reading comprehension among pre-intermediate English as Foreign Language (EFL) learners. A total of fifty female students, aged 17-18, from Esteghamat High School in Khoramshahr City, Iran, participated in the study. Participants were selected based on their performance on the Oxford Quick Placement Test (OQPT) and were randomly assigned to either an experimental group (n=25) or a control group (n=25). The experimental group was trained to use cognitive strategies, including summarizing, predicting, and making inferences during reading activities, while the control group continued with conventional reading methods. Data were collected through pre- and post-test assessments of reading comprehension. The results indicated that the experimental group significantly outperformed the control group, demonstrating improved reading comprehension skills. The findings suggest that the use of cognitive strategies, such as summarizing, predicting, and making inferences, can enhance EFL learners' ability to understand and retain reading material. The study concludes by discussing the implications for teaching practices, material development, and future research in the area of cognitive strategy training for reading comprehension.